Resiliensi perempuan dalam novel srepeg tlutur karya tiwiek SA - Pinasthika, Lintang Jayanti; Werdiningsih, Yuli Kurniati; Sunarya, Sunarya (Universitas PGRI Semarang, 2023)
The purpose of writing this study is to describe the resilience carried out by female characters in the novel Srepeg Tlutur by Tiwiek SA. The formulation of the problem in this study is how women's resilience in the novel Srepeg Tlutur by Tiwiek SA. The method in this study is qualitative, using feminism theory that focuses on the resilience of female characters. Research data in the form of words, phrases, and sentences containing elements of resilience of female characters in the novel Srepeg Tlutur by Tiwiek SA. Data collection techniques in the form of literature studies consisting of reading techniques and note-taking techniques. After the data is collected, data analysis techniques are used in the form of data reduction, data presentation, and data verification. The results of this study show the resilience characteristics of the novel Srepeg Tlutur by Tiwiek SA in the form of perseverance, calmness, independence, and self-awareness. There are also several traits possessed by resilient individuals in the novel Srepeg Tlutur by Tiwiek SA, namely social competence, and awareness of goals and the future. While the resilience factors in the novel Srepeg Tlutur by Tiwiek SA include emotional regulation, impulse control, optimism, causal analysis, self-efficacy, and recognition.